The SPTLC1 p.S331 mutation bridges sensory neuropathy and motor neuron disease and has implications for treatment. (10th August 2022) - Fiorillo, Chiara; Capodivento, Giovanna; Geroldi, Alessandro; Tozza, Stefano; Moroni, Isabella; Mohassel, Payam; Cataldi, Matteo; Campana, Chiara; Morando, Simone; Panicucci, Chiara; Pedemonte, Marina; Brolatti, Noemi; et al.
Abstract: Aims: SPTLC1 ‐related disorder is a late onset sensory‐autonomic neuropathy associated with perturbed sphingolipid homeostasis which can be improved by supplementation with the serine palmitoyl‐CoA transferase (SPT) substrate, l ‐serine. Recently, a juvenile form of motor neuron disease has been linked to SPTLC1 variants. Variants affecting the p.S331 residue of SPTLC1 cause a distinct phenotype, whose pathogenic basis has not been established. This study aims to define the neuropathological and biochemical consequences of the SPTLC1 p.S331 variant, and test response to l ‐serine in this specific genotype. Methods: We report clinical and neurophysiological characterisation of two unrelated children carrying distinct p.S331 SPTLC1 variants. The neuropathology was investigated by analysis of sural nerve and skin innervation. To clarify the biochemical consequences of the p.S331 variant, we performed sphingolipidomic profiling of serum and skin fibroblasts. We also tested the effect of l ‐serine supplementation in skin fibroblasts of patients with p.S331 mutations. Results: In both patients, we recognised an early onset phenotype with prevalent progressive motor neuron disease. Neuropathology showed severe damage to the sensory and autonomic systems. Sphingolipidomic analysis showed the coexistence of neurotoxic deoxy‐sphingolipids with an excess of canonical products of the SPT enzyme. l ‐serine supplementation in patient fibroblasts reduced production of toxic 1‐deoxysphingolipids but further increased the overproduction of sphingolipids. Conclusions: Our findings suggest that p.S331 SPTLC1 variants lead to an overlap phenotype combining features of sensory and motor neuropathies, thus proposing a continuum in the spectrum of SPTLC1 ‐related disorders. l ‐serine supplementation in these patients may be detrimental. Abstract : SPTLC1 spectrum disorder ranges from adult onset sensory neuropathy to childhood onset ALS and they are related to perturbed homeostasis of sphingolipids which can betreatable. Mutation of the S331 codon of SPLTC1 gene were related to a separate syndromic phenotype. This study provides clinical, neuropathological and biochemical evidences supporting the fact that S331 mutations actually result in an overlapping phenotype which bridges sensory neuropathy and motor neuron disease and alerts on treatment options.